2019
DOI: 10.1596/1813-9450-8746
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Rural Accessibility and Rural Roads Investment Needs Using Open Source Data

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 10 publications
0
15
0
1
Order By: Relevance
“…It is estimated that the Rural Access Index for sub-Saharan Africa is at 33.9% (World Bank 2016: p. 3). This index measures the fraction of people who have access to an all-season road within a walking distance of approximately 2 km (Mikou et al 2019).…”
Section: Development Of Agri-logisticsmentioning
confidence: 99%
“…It is estimated that the Rural Access Index for sub-Saharan Africa is at 33.9% (World Bank 2016: p. 3). This index measures the fraction of people who have access to an all-season road within a walking distance of approximately 2 km (Mikou et al 2019).…”
Section: Development Of Agri-logisticsmentioning
confidence: 99%
“…Current estimates of the RAI indicate that some 900 million rural dwellers worldwide do not have adequate access to a formal transport system (Roberts, Kc & Rastogi, 2006). Mikou et al (2019) used WorldPop population and Open Street Map network data to estimate the RAI and found that, assuming optimistic GDP growth, rural accessibility would only increase from 39 to 52 percent by 2030 across all developing countries. For this indicator, Mariathasan, Bezuidenhoudt & Olympio (2019) used Namibia as an example to calculate the possibility of road traffic through the global population grid.…”
Section: Introductionmentioning
confidence: 99%
“…The methods and calculations used to determine the Rural Accessibility Index have evolved quickly since its inception, and in recent years, driven also with advances in analytics, availability of geo-reference data, and computing power, several new methods have been developed (Transport & ICT 2016;Mikou et al 2019). To keep these methods simple and straightforward, the calculations of this index and the prioritization of interventions have been focusing on the origin of population, for example, where rural people live, but they do not consider the destination of that access and the facilities to which they are getting access.…”
Section: Introductionmentioning
confidence: 99%